Exceptionality Exclusion: Bridging Quantization and Relativity (Global Journal of Science Frontier Research, 2024)
The work on correcting the historically layered errors of Quantum Theory in addition to its specific corrections provided both an understanding of the reasons for their occurrence and why they were canonized And also it became obvious that the Scientific Misconceptions both included in the modern Quantum Theory and in Einstein s SRT have a General Character Therefore the Unified Theory as has now become obvious can and initially must be built on the General INVARIANTS of Quantization and the Principle of Relativity while each of the noted Theories proceeds from the use of an individual non-invariant set of orts plugging the holes of theories with EXCLUSIVITIES This work is devoted to their identification and elimination which will help correct both the FOUNDATIONS of the Theory of Relativity and will complement the corrections of the FOUNDATIONS of Quantization
Keywords: evidence-based physics; quantization; theory of relativity; subjective EXCLUSIVITY; INVARIANTS